Local food system disruptions: insights from the effect of COVID-19 on the livelihood of smallholder farmers in Koga irrigation scheme, Amara Region, Ethiopia - Gebreyes, Million; Müller-Mahn, Detlef; Teklu, Abyiot; Simane, Belay (Frontiers in Sustainable Food Systems, 2024)
The primary goal of this paper is to investigate the impact of COVID-19 on the livelihoods of smallholder farmers in Ethiopia. The study focused on how the pandemic impacted farmers’ access to markets, inputs, and labor, as well as their income and food security. The primary data consisted of panel data collected in three waves between 2018 and 2022. The three waves of data included pre-pandemic face-to-face interviews in August 2018, followed by phone surveys in June 2020 and November 2022. The study included a sample of 107 households from eight villages. The quantitative data was analyzed using descriptive statistics and an econometric analysis of difference-in-difference (DID) technique. The results show that the majority of farmers (76.6%) reported that COVID-19 has had a significant impact on their ability to purchase food from the market due to a variety of factors, including increased prices, limited availability of certain food items, disruption in supply chains, or reduced income for purchasing food. Disruptions in income-generating activities seriously affected farmers and their families, including financial hardship and food security concerns. Hence, 37, 32, 25, and 6 percent of farmers were mildly food secure, mildly food insecure, moderately food insecure, and severely food insecure, respectively. Reduction in household income was one of the most critical challenges farmers faced during the outbreak of the COVID-19 pandemic that affected food insecurity. As expected, the spread of the pandemic significantly reduced agricultural labor participation. Hence, households relying on income from agricultural labor have experienced worsened food insecurity. This suggests that the reduction in agricultural labor opportunities, potentially due to restrictions or disruptions caused by the pandemic, has had a negative impact on the food security of these households.